Aprossimazioni a Jewish voices from arab countries in contemporary italian prose - Lalicata, Maria (Dialogoi. Rivista di studi comparatistici, 2020)
The aim of this article is to disseminate and at the same time promote new insights on the voices, in Italian, of authors belonging to Jewish communities from Arab countries, that enrich with their works the contemporary Italian literature of emigration. A phenomenon that has been recorded since the 1990s, whose themes relate to the Sephardic origin, collective and individual historical migration, the process of formation of identities in the host culture. Themes expressed in a porous Italian open to influences of Arabic, Hebrew, Ladin, English and French.